2020
DOI: 10.1007/s11356-020-10767-3
|View full text |Cite
|
Sign up to set email alerts
|

Environmental exposure to persistent organic pollutants measured in breast milk of lactating women from an urban area in central Poland

Abstract: Mothers’ milk is considered a channel by means of which new-borns are exposed to polychlorinated dibenzo-p-dioxins (PCDDs), polychlorinated dibenzofurans (PCDFs), and dioxin-like polychlorinated biphenyls (dl-PCBs), environmental pollutants entering food chain and accumulating in fat-rich tissues. In this study, the concentrations of selected PCDDs, PCDFs, and dl-PCBs (a total of 29 substances) in milk samples of 110 breast-feeding women from an urban area were analyzed using the high-resolution gas chromatogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The findings of the current study revealed that the highest proportions of PCB-118 and PCB-105 were found in farm crabs (51.8% and 19.8%) and in market crabs (51.2% and 18.3%). Compared to PCDD/Fs, DL-PCBs were abundantly produced and used in the past, and they are relatively difficult to degrade under the influence of physical and chemical factors [ 28 ]. The most decent explanation for the above statement may be that the presence of residual PCB-118 and PCB-105 in crab may make DL-PCBs more stable.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of the current study revealed that the highest proportions of PCB-118 and PCB-105 were found in farm crabs (51.8% and 19.8%) and in market crabs (51.2% and 18.3%). Compared to PCDD/Fs, DL-PCBs were abundantly produced and used in the past, and they are relatively difficult to degrade under the influence of physical and chemical factors [ 28 ]. The most decent explanation for the above statement may be that the presence of residual PCB-118 and PCB-105 in crab may make DL-PCBs more stable.…”
Section: Discussionmentioning
confidence: 99%
“…Four journal articles discovered a correlation between age and POPs levels where cis-Chlordane, dichloro-diphenyl dichloro-ethylene (DDE), and PCB were found in breast milk, whereas older individuals have higher POPs levels (9,14,30,39). Chlordane is a type of OCPs and is widely used as an insecticide.…”
Section: Agementioning
confidence: 99%
“…It has been noted that the main source of POPs presence in the human specimens is a dietary habit (30). A total of eight studies discovered associations between dietary habits and POPs levels in human specimens, and the sample used in all those studies is breast milk.…”
Section: Dietary Habitsmentioning
confidence: 99%
See 2 more Smart Citations